‘No woman’s land’: A study of women’s land rights in context of neoliberal dispossession and gender relations in India - Sharma, Devika; Bhagat, Lakshita (My University, 2024)
Given the complex web of socio-cultural factors, intersectional features of gender identity and the recent trajectories of a lack of land resources, the rise of alternative gainful employment, and a feminization of agriculture, this paper investigates whether land rights are the ultimate panacea for women’s autonomy. Land can be a source of women’s empowerment albeit the patriarchal Indian society restricts women’s right to property. Women in India are not a homogenous category. They are defined by their intersectional identities of caste, class, ethnicity, stages in their life course and subjectivities regarding demands for land. A more nuanced approach to women’s land rights is proposed in view of the agrarian crisis, restricted social validity of women’s land claims and other factors. Research has been conducted including an analysis of various feminist and intersectional debates concerning land rights in India, government reports, legal judgements, and religious text, among others.
Keywords: gender norms; Indien; intersectionality; Intersektionalität; land rights; neoliberal dispossession; Neoliberalismus; women; ddc:300